Measurement of biomechanical interactions at the stump-socket interface in lower limb prostheses - Noll, V.; Wojtusch, J.; Schuy, J.; Grimmer, M.; Rinderknecht, S.; Beckerle, Philipp (Proceedings of the Annual International Conference of the IEEE Engineering in Medicine and Biology Society, EMBS, 2015)
This paper introduces a novel measuring approach for detecting relative movement between stump and socket in lower limb prostheses. The application of the motion capturing based measuring approach is shown at a single male transtibial amputee using a Patella Tendon Bearing (PTB) socket. It further investigates and assesses the feasibility of measuring the relative movement between stump and socket during level walking at different velocities and allocating it to the coinciding loads. Representative results for the two translational degrees of freedom in the sagittal plane are presented and discussed. For the proximodistal (pd) direction, a linear correlation between applied load and relative movement is found, while for the anteroposterior (ap) direction the stump movement is largely influenced by the motion sequence during the respective gait event. Additionally, the effect of walking speed is discussed.
CRIS-Team Scopus Importer:2021-09-24